Nuel Belnap on Indeterminism and Free Action. - Müller, Thomas; Müller, Thomas (Cham : Springer International Publishing AG, 2014)
Featuring critical assessments of Belnap's work, and a paper by the celebrated philosopher himself on case-intensional first order logic, this selection of original research on a much-debated topic charts his impact on the discussion and builds on his ideas.
2 Preliminaries: The STIT Framework -- 3 Modeling Choice Situations -- 3.1 The Modal Heart of Choice -- 3.2 An Initial Comparison with Modal Logics of Action -- 3.3 Merging the Two Perspectives on Action -- 4 A Merged System: Matrix Game Logic -- 4.1 Modal logic of matrix games -- 4.2 STIT in Modal Matrix Logic -- 4.3 Complexity and Correlation -- 5 The Roles of Knowledge -- 6 Dynamic Epistemic Logic Meets STIT -- 7 Further Directions -- 8 Conclusion -- References -- 15 Intentionality and Minimal Rationality in the Logic of Action -- 1 Analysis of Propositional Contents of Attitudes -- 2 My New Approach in the Logic of Propositional Attitudes -- 2.1 Analysis of Psychological Modes and Possession Conditions of Attitudes -- 2.2 Analysis of Satisfaction Conditions of Propositional Attitudes -- 3 Intentionality in the Logic of Action -- 4 Fundamental Valid Laws -- References -- 16 Group Strategies and Independence -- 1 Stit Frames -- 2 Outcomes -- 3 Fields and Outcomes Bordering Fields -- 4 Strategies and Their Admitted Future Outcomes -- 5 Pre-Simple Strategies and Complete Strategies -- 6 Group-Joining Meets -- 7 Distinguishability -- 8 Inactivity and Busyness -- 9 Independence -- References -- 17 Biographical Interview -- 1 School Days -- 2 From BA at Illinois to Grad School at Yale -- 3 From Yale to Pittsburgh -- 4 Employment History at Pitt -- 5 Visiting Professorships -- 6 Professional Service -- 7 Journals -- 8 Prizes and Fellowships -- 9 Honors -- 10 Doctoral Students -- 11 Publications.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books